(untitled) (The Peerian Journal, 2022)
To identify dements and reveal the techniques used by the author to illustrate racial discrimination and injustice. This work includes several tasks that will be clarifying: to give general information; to give brief information of the evidence of the Harlem period in America; to explain about that period in America. In this research include historical, biographic, analytical, descriptive and comparative methods.